Early events of canine herpesvirus 1 infections in canine respiratory and genital mucosae by the use of ex vivo models. (April 2016) - Li, Yewei; Negussie, Haileleul; Qiu, Yu; Reddy, Vishwanatha R.A.P.; Mateusen, Bart; Nauwynck, Hans J.
Abstract: Canine herpesvirus 1 (CaHV-1) causes a systemic disease in newborn puppies, kennel cough at all ages and genital lesions in adult dogs. The aim of the present study was to elucidate the viral behavior during the early stage of infection in respiratory and genital mucosae, the portals of entry for CaHV-1 by the use of ex vivo explants. CaHV-1 infected and replicated in respiratory and vaginal mucosae in a plaque wise manner. CaHV-1 started to penetrate the basement membrane (BM) only after 48 h post inoculation (hpi) in respiratory mucosal explants, but already after 24 hpi in vaginal explants. The plaque latitude and penetration depth increased over time and both were larger in the vaginal explants compared to the respiratory mucosal explants. The canine respiratory and genital mucosal explants were suitable to study the early pathogenesis of CaHV-1. CaHV-1 showed a better capacity to replicate and invade vaginal mucosa compared to respiratory mucosa, based on the latitude and penetration depth of the plaques of viral antigen positive cells.